The ratio of the contribution of some biomechanical variables and indicators to the achievement of the effectiveness of the high jump with (Fosbury Flop) as an indicator to determine the efficiency of the starting variables - Khaleel Ibrahim Alsudani, Atheer (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the value of some of the variables represented by the angle of inclination of the body at the moment of rise, the height of the center of mass of the body, the angle and velocity of departure, the highest strength of the moment of rise, the time of momentary thrust, the moment of rise, the angular momentum of the trunk, the angular momentum of the thigh of the weighted man The angular momentum of the leg of the weighted leg, the angular momentum of the leading arm), the biomechanical indicators of movement flow, the momentary ability to rise, the kinetic energy of the trunk, and the identification of the percentage of contribution to the achievement, as the research problem embodied in finding a contribution rate for some variables and biomechanical indicators related to the main section stage) Standing and advancement) as a criterion for evaluating the effectiveness of the launch to the achievement of the effectiveness of the high jump in the (Fosbury Flop) simultaneously in order to research the parts of the skill of performance and to reach the accuracy of technical performance that serves sports achievement and work to develop it because it is related to the correct biomechanical conditions associated with the performance of the event. Descriptive approach, correlational relations, and the sample consisted of 12 hopers who accounted for 75% of the research community. (CASIO) type number (3) with high speed (120 images/second), and the values of the search variables were extracted through imaging using the kinematic analysis program (Kinovea 8.25), and the data results were presented, analyzed, and discussed to extract the value of the correlations for the variables and achievement rates. The following conclusions were reached (the ratio of the contribution of the variables, velocity and starting angle, the highest strength of the moment of rise, as for the biomechanical indicators, the angular momentum of the weighted leg of the leg, the movement flow, the momentary ability to rise), and the researcher recommended (the importance of strengthening and supporting the capabilities of trainers by including them in Various workshops and work sessions to identify the importance of applying physical and mathematical laws and kinematic analysis, he conducted similar studies and supported them with biomechanical variables and indicators of the body over the crossbar in proportion to the anthometric measurements, the necessity of conducting similar researches, a few physical exercises - skilled with perception - kinesthetic).